Determinants of treatment failure among tuberculosis patients in Kandahar City, Afghanistan: A 5-year retrospective cohort study - Bilal Ahmad Rahimi (2020)
Background: Tuberculosis (TB) is a preventable and treatable chronic disease. Afghanistan is among the high-TB-burden countries. The aim of this study is to find the determinants of treatment failure among TB patients in Kandahar City, Afghanistan. Methods: This was a retrospective cohort study conducted in Kandahar City during a period of 5 years (August 2014-July 2019). For data analysis; descriptive statistics, Chi-square test, and logistic regression were used. Results: Among 1416 TB patients, 894/1416 (63.1%) had pulmonary TB (PTB), whereas 522/1416 (36.9%) had extrapulmonary TB (EPTB). Mean age in these patients was 34.7 years while most of them were females in PTB (530/894 [59.3%]) and EPTB (340/522 [65.1%]) patients. Sputum smear was positive in 618/860 (71.9%) and 16/404 (4%) of PTB and EPTB patients, respectively. TB treatment failure was more in PTB (56/894 [6.3%]) than EPTB (4/522 [0.8%]). Chi-square test of TB cases showed that statistically significant determinants that may cause the treatment failure were re-treatment cases (crude odds ratio [COR] 7.7, P < 0.001), absence of fever (COR 5.2, P < 0.001), absence of cough (COR 1.7, P = 0.004), living in rural areas (COR 1.4, P = 0.035), and no weight loss (COR 1.3, P = 0.033). Binary logistic regression of the statistically significant variables revealed only absence of fever (adjusted odds ratio 6.0, P < 0.001) as the risk factor for treatment failure in TB patients. Conclusion: TB is still a major threat for Kandahar City. Low treatment success rate and increased number of defaulted cases are the major threats.